Presentasi Mahasiswa di Perguruan Tinggi: Pengucapan dan Pemakaian Bahasa Indonesia Berbasis Penilaian Diri Sendiri: Indonesian Pronunciation and Language Use in University Student Presentations: A Self-Assessment Approach - Wijayanti, Sri Hapsari; Panjaitan, Yunia; Pramono, Herry (Information Technology and Science(ITScience), 2025)
Oral speaking skills, particularly presentation skills, are continuously developed and improved throughout higher education so that students gain courage, confidence, and the ability to articulate their thoughts and opinions to others. Presentation skills are also a key requirement for university graduates entering the professional world. This study aims to examine students’ spoken utterances and oral language use during academic presentations at a private university in Jakarta, Indonesia. The research employs both qualitative and quantitative descriptive approaches. Data collection was conducted from May to July 2025, involving 122 student respondents. Qualitative data were obtained through observation and documentation in the form of recorded presentation videos. Quantitative data were collected using a Likert-scale questionnaire with four response options ranging from strongly disagree to strongly agree. The findings indicate that in the aspect of speaking, more than 50% of the respondent's paid attention to clarity of articulation, emphasized important words, and adjusted their speech so it was neither too loud nor too soft. Additionally, more than 70% acknowledged that they regulated their volume appropriately and avoided monotonous intonation. However, regarding the use of formal Indonesian, 66% of respondents still mixed formal Indonesian with colloquial or conversational language; 44% continued to insert English words; and 35% still confused the use of the pronouns kita and kami. The study concludes that presentations in higher education are not merely the act of delivering material but also require careful control of stress, intonation, rhythm, and tempo, as well as the appropriate use of formal spoken Indonesian.